Altruistic Preferences and Empathic Concern among Generation Z Pre-Service Teachers: The Moderating Role of Self-Control - Noviani, Leny; Amanda, Khofifah Tria; Oktaviani, Leny Kurnia (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to analyse the effect of altruistic preferences on empathic concern and examine the moderating role of self-control among Generation Z pre-service teachers. A quantitative approach with a cross-sectional design was employed. The study population comprised 1,833 students enrolled in Economic Education Study Programs at Universitas Sebelas Maret (UNS) and Universitas Negeri Semarang (UNNES). The sample was selected using purposive and proportional random sampling, yielding 177 valid responses. Data were collected through an online Likert-scale questionnaire and analysed using Moderated Regression Analysis (MRA) in SPSS. The results indicate that altruistic preferences have a positive and significant effect on empathic concern (p < 0.001). Self-control also has a significant direct effect on empathic concern (p = 0.028); however, it does not significantly moderate the relationship between altruistic preferences and empathic concern (p = 0.762). These findings suggest that empathic concern among Generation Z pre-service teachers is directly associated with altruistic preferences, whereas self-control does not significantly alter this relationship. The findings provide an empirical basis for strengthening character education and social-emotional competencies in teacher education.